Attenuated immune surveillance during squamous cell transformation of pancreatic adenosquamous cancer defines new therapeutic opportunity for cancer interception - Jie Chen; Xianlong Chen; Xinyuan Chen; Shanyue Sun; Shuofeng Li; Shuangni Yu (Journal for ImmunoTherapy of Cancer)
Background Pancreatic adenosquamous cancer (PASC) is an extremely rare subtype of pancreatic cancer characterized by a poorer prognosis and higher likelihood of metastasis compared with the more prevalent pancreatic ductal adenocarcinoma (PDAC). Although genomic changes during PASC tumorigenesis have been documented, the corresponding alterations in the tumor immune microenvironment (TIME) remain inadequately elucidated. Therefore, this study aims to analyze the immune landscape of PASC by employing multiplex immunohistochemistry (mIHC) and digital image analysis.Methods In this study, we analyzed four independent cohorts comprising 120 patients with PASC and 386 patients with PDAC. We employed mIHC to quantify three in situ panels of immuno-oncology-related biomarkers at subcellular resolution. We then used five samples to perform laser capture microdissection, RNA sequencing, and whole-exome sequencing to explore the underlying mechanisms of the compartment-specific immune phenotypes in PASC.Results Our findings revealed a more immunosuppressive TIME in PASC compared with PDAC, characterized by a decreased abundance of T cells. Immune cell types indicative of enhanced immune surveillance, including cytotoxic and memory T cells and antigen-experienced T cells, were present at significantly lower densities in PASC compared with PDAC. Conversely, some immunosuppressive macrophage phenotypes exhibited increased distribution in PASC. Immunosuppressive immune cells (ICs) were abundant, enriched within stromal regions, highly heterogeneous across tumors, and exhibited distinct distributions between squamous cell (SQC) and adenocarcinoma (ADC) compartments in PASC. Notably, the TIME of SQC compartments harbored more exhausted T cells compared with synchronous ADC compartments, indicating attenuated immune surveillance during squamous transformation. Transcriptomic profiling of microdissected SQC and ADC regions revealed immune exhaustion signatures and downregulated T-cell differentiation pathways in SQC compartments, alongside altered antigen presentation machinery and elevated tumor mutational burden, suggesting squamous-specific tumor-associated antigens with potential immunotherapeutic relevance. Beyond differences in IC density, we observed closer spatial proximity of CD45RO+ and PD-1+CD3+CD8+ T cells to tumor cells within 10, 20 and 30 µm ranges in PASC compared with PDAC, with variations by histological subregion. Furthermore, we found distinct expression patterns of the programmed cell death protein-1 (PD-1)/programmed death ligand 1 (PD-L1) and T-cell immunoreceptor with immunoglobulin and the ITIM domain (TIGIT)/CD155 axes in the PASC TIME associated with survival outcomes. Notably, TIGIT+CD8+ T cells and CD155+ CD68+macrophages, along with their proximity to tumor cells, served as independent prognostic indicators. These findings were validated in an independent cohort study.Conclusion Our study advances the understanding of PASC by providing updated insights into its immunoenvironmental features. These findings underscore the potential of targeting immune checkpoint pathways, particularly the TIGIT/CD155 and PD-1/PD-L1 axes, as a therapeutic strategy for PASC.